Ecolinguistics: Towards a new harmony. (July 2017) - Zhou, Wenjuan
Abstract: In this paper, I argue that only dialogue that links science, aesthetics, and axiology can solve the ecological crisis' moral concerns. Serious consideration can thus be given to raising bio-ecological awareness (Section 1). The paper traces three global waves in the emerging field of ecolinguistics (Section 2). Their divergences and disharmony have hindered awareness of the bio-ecology and the benign development of the discipline (Section 3). To bring clarity to the field, it is therefore proposed that the roots of disharmony tap into the moral and ethical harmony of Chinese worldview (Section 4). By adopting a harmonious view of language, mind and the world, a future harmonious ecolinguistics can be realized to become a life science (Section 5). In short, a synthesis of science, axiology and aesthetics can bring new harmony to European and Chinese ecolinguistics. Such an outcome would be a significant step in improving human bio-ecological awareness and resolving the ecological crisis (Section 6). Highlights: A new harmony for a future harmonious ecolinguistics as a life science is proposed. Ecolinguistics should counter the Newtonian–Cartesian worldview and rethink the discipline as a life science. Chinese worldview of harmony can help ecolinguistics engage in bio-ecological awareness and deal with ecological crisis. The new harmonious agenda relies on a harmonious view of language, mind and the world. A new harmony of science, axiology and aesthetics can improve bio-ecological awareness and resolve the ecological crisis.